Causal Effects between Gut Microbiome and Myalgic Encephalomyelitis/Chronic Fatigue Syndrome: A Two-Sample Mendelian Randomization Study - He, Gang; Cao, Yu; Ma, Honghao; Guo, Siran; Xu, Wangzi; Wang, Dai; Chen, Yongquan; Wang, Houzhao (Frontiers in Microbiology, 2023)
Background: Evidence from previous studies have implicated an important association between gut microbiota (GM) and Myalgic Encephalomyelitis/ Chronic Fatigue Syndrome (ME/CFS), but whether there is a definite causal relationship between GM and ME/CFS has not been elucidated. Method: This study obtained instrumental variables of 211 GM taxa from the Genome Wide Association Study (GWAS), and mendelian randomization (MR) study was carried out to assess the effect of gut microbiota on ME/CFS risk from UK Biobank GWAS (2076 ME/CFS cases and 460857 controls). Inverse variance weighted (IVW) was the primary method to analyze causality in this study, and a series of sensitivity analyses was performed to validate the robustness of the results.The inverse variance weighted (IVW) method indicated that genus Paraprevotella (OR:1.001, 95%CI:1.000-1.003, p-value<0.05) and Ruminococca-ceae_UCG_014(OR 1.003, 95% CI 1.000 to 1.005, p-value < 0.05) were positively associated with ME/CFS risk. Results from the weighted median method supported genus Paraprevotella (OR 1.003, 95% CI 1.000 to 1.005, p-value < 0.05) as a risk factor for ME/CFS. Conclusions: This study reveals a causal relationship between genus.paraprevotella, genus.Ruminococcaceae_UCG_014 and ME/CFS, and our findings provide novel insights for further elucidating the developmental mechanisms mediated by the gut microbiota of ME/CFS.